Menstrual cups to reduce bacterial vaginosis and STIs through reduced harmful sexual and menstrual practices among economically vulnerable women: protocol of a single arm trial in western Kenya - Garazi Zulaika; Fredrick O. Otieno; Linda Mason; Anna Maria van Eijk; Runa Bhaumik; Stefan J. Green; Penelope A. Phillips-Howard; Supriya D. Mehta (BMC, 2024)
Abstract Background In western Kenya, menstrual hygiene management (MHM) is a pervasive problem. Challenges are compounded for economically constrained women who continue to engage in sex during menses and resort to practices such as vaginal insertion of tissue and cotton to maintain dryness during sex. These practices can be harmful to the vaginal microbiome (VMB) and can lead to high rates of sexually transmitted infections (STIs) and HIV. This study will evaluate whether menstrual cups that can be worn during intercourse may be beneficial to the VMB and help prevent Bacterial vaginosis (BV) and STI acquisition among these economically vulnerable women. Methods In this single-arm trial among economically vulnerable women in semi-urban western Kenya, we will evaluate the preliminary efficacy of menstrual cups on non-optimal VMB, BV, and STIs, and investigate safety, acceptability, and implementation needs. Through peer referral we aim to recruit 402 menstruating women aged 15-35 who exchange sex for money or basic needs. Women who are pregnant, have delivered in the past six months, or use an intrauterine device (IUD) will not be eligible. Participants will be seen every six months for 24 months and be asked about their sexual and MHM practices, with samples collected to assess BV and VMB. At baseline, 12-, and 24-month visits, additional samples will be collected to measure HIV and STIs (C. trachomatis, N. gonorrhoeae, and T. vaginalis). HSV-2 status will be assessed at baseline. Intervention provision will consist of one reusable disc-shaped menstrual cup per participant and a group-based training within four weeks of the 12-month visit, followed by monthly telephone surveys for the first three months to assess cup use, adverse events, and provide any assistance. Primary analyses of preliminary efficacy will compare probabilities of optimal VMB, BV, and STIs in the pre-intervention period to the post-intervention period. Primary safety analyses will compare occurrence of menstrual toxic shock syndrome and cervicovaginal laceration. Discussion If demonstrated safe and effective, this multipurpose reproductive health intervention will offer a dignified solution for the menstrual hygiene needs of women who engage in sex for livelihood and reduce their occurrence of non-optimal VMB, BV, and STIs. Trial registration Clinicaltrials.gov NCT05666778 (28th December, 2022); Pan African Clinical Trials Registry 202,305,912,778,108 (25th May, 2023).